Knockdown of adipokinetic hormone synthesis increases susceptibility to oxidative stress in Drosophila--a role for dFoxO? - Bednářová, Andrea; Kodrík, Dalibor; Krishnan, Natraj (Comparative biochemistry and physiology. Toxicology & pharmacology, 2015)
Insect adipokinetic hormones (AKHs) are pleiotropic hormones known to play a protective role in response to oxidative stress (OS). However, the precise signaling pathways are unclear. We present evidence that AKH may primarily employ the Forkhead box class O transcription factor (FoxO) to exert this effect. The impact of knocking down AKH synthesis or its over-expression in its response to OS was studied in Drosophila melanogaster. AKH knockdown (AKH-RNAi) as well as AKH overexpression (AKH-oex) was achieved using the Gal-4/UAS system and controls were w(1118) (+/+), AKH-Gal4/+, UAS-AKH/+ and UAS-AKH-RNAi/+. Exposure to 80 μM hydrogen peroxide (HP) revealed that AKH-RNAi flies showed significantly higher mortality than AKH-oex or the respective control lines. This susceptibility was evidenced by significantly enhanced levels of protein carbonyls - a biomarker of OS, in AKH-RNAi flies compared to controls and AKH-oex flies. Interestingly, AKH-oex flies had the least amount of protein carbonyls. AKH-RNAi flies had significantly less dFoxO transcript and translated protein compared to control and AKH-oex flies in un-challenged condition as well as when challenged with HP. Sestrin - a major antioxidant defense protein and one of the targets of dFoxO - was also significantly down-regulated (both at mRNA and protein level) in AKH-RNAi flies (both unchallenged and challenged with HP) compared to control flies and flies with over-expressed AKH. These findings imply that dFoxO may act downstream of AKH as a transcription factor to mediate response to OS in D. melanogaster.
Keywords: FoxO; Forkhead Transcription Factors; Oxidative Stress; Drosophila melanogaster; oxidační stres; Heat-Shock Proteins; messenger RNA; Crosses, Genetic; léková rezistence; regulace genové exprese; Oxidative stress; Oligopeptides; forkhead transkripční faktory; geneticky modifikovaná zvířata; Drosophila Proteins; Protein Carbonylation; oxidancia; Biomarkers; Recombinant Proteins; zvířata; karbonylace proteinů; oligopeptidy; Adipokinetic hormone; křížení genetické; proteiny Drosophily; rekombinantní proteiny; Animals, Genetically Modified; RNA, Messenger; biologické markery; Gene Expression Regulation; Male; hmyzí hormony; peroxid vodíku; Drug Resistance; Hydrogen peroxide; Insect Hormones; RNA Interference; Drosophila; Oxidants; MAP Kinase Signaling System; Animals; mužské pohlaví; RNA interference; Hydrogen Peroxide; Pyrrolidonecarboxylic Acid; MAP kinasový signální systém; kyselina pyrrolidonkarboxylová; proteiny teplotního šoku